A sensitivity study of parameters affecting residual stress predictions in finite element modelling of the inertia friction welding process - Iracheta, Omar; Bennett, Chris; Sun, Wei (Elsevier, 2015)
This study presents a finite element (FE) model capable of predicting the final residual stress field in an inertia friction welded component of a CrMoV steel considering the elastic and inelastic components of strain resulting from mechanical deformation, temperature changes in the material and volumetric changes associated with phase transformations. The material database was improved to include the properties of the child phases involved in the polymorphic transformation during inertia friction welding (IFW) of CrMoV steels, i.e. austenite and quenched martensite, taking different approaches based on existent experimental data from the parent phase (tempered martensite) and material characterisation of the heat affected zone (HAZ) in weld trials. This is the only FE model available in the literature that takes into consideration the effects induced by the transformation strain component of multiple phases in the total strain generated during IFW. Several simulations were run using this FE model in order to address for the first time the sensitivity of the final residual stress field to the individual effects of the microstructural changes, the interrelationship of multiple phases, and to different processing parameters such as the die geometry, clamping history and cooling rates.